2022
DOI: 10.3390/s22124452
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Blood Glucose Estimation System Based on a Neural Network with Dual-Wavelength Photoplethysmography and Bioelectrical Impedance Measuring

Abstract: This study proposed a noninvasive blood glucose estimation system based on dual-wavelength photoplethysmography (PPG) and bioelectrical impedance measuring technology that can avoid the discomfort created by conventional invasive blood glucose measurement methods while accurately estimating blood glucose. The measured PPG signals are converted into mean, variance, skewness, kurtosis, standard deviation, and information entropy. The data obtained by bioelectrical impedance measuring consist of the real part, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, the researchers stated that further research is needed to understand the ideal frequency range for measuring glucose levels. Similarly, Yen, Chen [41] demonstrated improved accuracy with the proposed combination of dual-wavelength PPG and BIS in the frequency range of 50 and 100 kHz placed between the index and middle fingers as well as under the wrists while using a Back Propagation Neural Network algorithm. However, it is important to consider the wrist circumference and wrist temperature, as well as body weight, as physiological parameters that can impact the accuracy of non-invasive glucose measurements [50].…”
Section: Bio-impedance Spectroscopy (Bis)mentioning
confidence: 83%
See 2 more Smart Citations
“…However, the researchers stated that further research is needed to understand the ideal frequency range for measuring glucose levels. Similarly, Yen, Chen [41] demonstrated improved accuracy with the proposed combination of dual-wavelength PPG and BIS in the frequency range of 50 and 100 kHz placed between the index and middle fingers as well as under the wrists while using a Back Propagation Neural Network algorithm. However, it is important to consider the wrist circumference and wrist temperature, as well as body weight, as physiological parameters that can impact the accuracy of non-invasive glucose measurements [50].…”
Section: Bio-impedance Spectroscopy (Bis)mentioning
confidence: 83%
“…Yen, Chen [41] found that combining dual-wavelength PPG with another method, such as Bioelectrical Impedance (BI), delivered quantitative results. Although BI does not directly measure glucose levels, it can provide information about body composition and fluid distribution (i.e., body fat, mass, and water).…”
Section: Photoplethysmography (Ppg)mentioning
confidence: 99%
See 1 more Smart Citation
“…Blood glucose has different absorption rates of different lights and these data are used to calculate the blood glucose. [ 17 ] A previous study showed that GlucoTrack can detect blood glucose from the ear lobe with clinical accuracy. However, this device is not available to Indian consumers.…”
Section: Discussionmentioning
confidence: 99%